Part-load characteristics of a new ammonia/lithium nitrate absorption chiller. (August 2015) - Zamora, Miguel; Bourouis, Mahmoud; Coronas, Alberto; Vallès, Manel
Abstract: A pre-industrial prototype of a new water-cooled ammonia/lithium nitrate absorption chiller was characterised at part-load operation mode. The chiller was built using brazed plate heat exchangers in all its components, including the absorber and the generator. A test campaign was carried out varying the thermal load in the chilled water circuit and keeping the hot and cooling water temperatures constant. Part-load curves of the thermal and electrical coefficients of performance were obtained, plotted and compared with data from the literature on small capacity absorption chillers with conventional working pairs, namely ammonia/water and water/lithium bromide. The experimental results showed that to achieve a higher electrical coefficient of performance at part-load operation, it was much more convenient to use an ON-OFF control than to modify the hot water temperature. Furthermore, using a simple ON-OFF control strategy, the behaviour of the new absorption chiller was more agile and responded more quickly. The part-load curve of the electrical coefficient of performance was obtained by adjusting the experimental data to the shape of the curve proposed in the standard prEN-14825:2011 for air-to-water chillers. The Cc coefficient was 0.7985 matching the value obtained dividing the remaining electrical consumption measured during the OFF half cycles by the total energy consumption generated. Highlights: A new NH3 /LiNO3 absorption chiller was experimentally characterized at part-load. Thermal and electrical coefficients of performance at part-load were obtained. Degradation of the electrical COP operating with an ON-OFF control was analyzed. The chiller presented a fast response due to the use of plate heat exchangers.